The Effect of Tax Revenue and Inflation on Economic Growth in Indonesia 1994-2024 - Dyah, Tri Murti Ayu; Yunus, Rita; Sading, Yunus; Jaya, Andi Herman; Musdayati, Musdayati (Transpublika Publisher, 2025)
This research seeks to examine and evaluate how tax revenue and inflation impact Indonesia's economic growth from 1994 to 2024. The researchers employed an explanatory methodology with a quantitative framework, utilizing time series secondary data sourced from Indonesia's Central Statistics Agency (BPS). The analytical approach involved multiple linear regression analysis conducted through Eviews 12 software, complemented by t-tests and F-tests to assess the statistical significance of how independent variables influence the dependent variable. The findings reveal that when examined individually, tax revenue demonstrates a positive and statistically significant relationship with economic growth, while inflation shows a negative but statistically insignificant relationship with Indonesia's economic growth during the study period. When analyzed collectively, both tax revenue and inflation variables demonstrate a positive and statistically significant combined effect on Indonesia's economic growth throughout the 1994-2024 timeframe.